Modern Latin America - Thomas E Skidmore (Oxford Univ. Press, 1992)
The book examines the implications of the end of the Cold War on U.S.-Latin American relations, such recent developments as international drug trafficking, and the ongoing trend away from authoritarian regimes towards civilian leaders abd elected governments. The book illustrates such central themes as European-Indian and European-African interaction, large-scale immigration in the late 19th and 20th centuries, populist political leadership, military takeovers, and U.S. intervention in Latin America, examining the influence of economic forces and social tensions on political conflict in each case and in clear, jargon-free language